Bone Marrow Adipocytes: A Critical Player in the Bone Marrow Microenvironment - Wang, Lipeng; Zhang, Hao; Wang, Sicheng; Chen, Xiao; Su, Jiacan (Frontiers in Cell and Developmental Biology, 2021)
Recognized for nearly 100 years, bone marrow adipocytes (BMAs) form bone marrow niches that contain hematopoietic and bone cells, the roles of which have long been underestimated. Distinct from canonical white, brown, and beige adipocytes, BMAs derived from bone marrow mesenchymal stromal cells possess unique characteristics and functions. Recent single cell sequencing studies have revealed the differentiation pathway and seminal works support the tenet that BMAs are critical regulators in hematopoiesis, osteogenesis and osteoclastogenesis. In this review, we discuss the origin and differentiation of BMAs, as well as the roles of BMAs in hematopoiesis, osteogenesis, osteoclastogenesis and immune regulation. Overall, BMAs represent a novel target for bone marrow-related diseases, including osteoporosis and leukemia.